HUBUNGAN STATUS GIZI DENGAN KESEGARAN JASMANI SISWA SD NEGERI 004 TELUK NILAP KECAMATAN KUBU BABUSSALAM - Juni Rafianto; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the lack of physical fitness that is owned by students SDN 004 Teluk Nilap. Of the school activity seen many students are lazy and some sickly. This problem can be seen from the observation of researchers during learning procces in school, it is suspected because of the nutritional status held by students. Therefore, the purpose of this study was to determine the corelation between nutritional status and physical fitness of students of SD Negeri 004 Teluk Nilap Kubu Babussalam District. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is the nutrition status, while the dependent variable (Y) is physical fitness. The research data was obtained from measurements of height and weight of students and tests TKJI. The sample in this study were male students keals IV and V which totaled 33 people (total sampling). Based on the research results can be concluded as follows: there is a significant corelation between nutritional status and physical fitness of students of SD Negeri 004 Teluk Nilap Kubu Babussalam district where rhit (0.51)> rtab (0.334).Keywords : Nutrition Status, Physical Fitness